Subcritical water extraction for the isolation and identification of phytochemicals from piper betle leaves - Taysir Abdelrhman Musa Adam, 1971-; Mohd. Marsin Sanagi, supervisor; Wan Aini Wan Ibrahim, supervisor; Farediah Ahmad, supervisor; Fakulti Sains (2013)
Thesis (Ph.D (Kimia)) - Universiti Teknologi Malaysia, 2013